A Question of Leadership Does Shared Leadership Reduce Individual Responsibility and Accountability? - Steed, Judith; Steed, Judith; Laskow, Greg (Center for Creative Leadership, 2003)
Shared leadership can increase individual responsibility and accountability. But shared leadership can be achieved only when it is the appropriate way to manage the work, when managers and employees are appropriately trained and developed to participate in it, when organizational systems are properly aligned to foster and reward it, and when organizational culture promotes it.